GAMBARAN POLA MENU DAN HUBUNGAN TINGKAT ASUPAN ZAT GIZI MAKRO DAN KEPUASAN PELAYANAN MAKANAN DENGAN STATUS GIZI REMAJA SANTRI PUTRI - Rohmah, Mazidatur (Jurnal Mitra Kesehatan, 2023)
Introduction : Bustanul ulum Islamic Boarding School is religious education provider that manages the provision of food. A good food organization system consists of varied menu, can meet nutritional needs, and fulfill santri satisfaction. This can determine the value of the nutritional status of students. This study aims to determine the description of menu patterns and the relationship between the level of macronutrient intake and the level of satisfaction food service with the nutritional status of female students at Pondok Pesantren Bustanul Ulum. Method: This type of research is an observational analytic quantitative research with cross-sectional approach. The sampling method used simple random sampling with 57 samples. The data analysis technique uses the Spearman rank test. The results of observations of the food menu showed that the menu pattern of Bustanul Ulum Islamic Boarding School needed to be more varied. Result: The statistical test results showed the level of protein intake (p = 0,127), fat intake (p = 0,299), and carbohydrate intake (p = 0,275), and the level of satisfaction food service (p = 0.784) with nutritional status. Conclusion: The test results conclude that there is no relationship between the level of macronutrient intake and the level of satisfaction food service with the nutritional status.